ARTEFACTS FROM KRAKOW-NOWA HUTA AS AN ILLUSTRATION OF SELECTED ISSUES OF RESEARCH INTO PREHISTORIC AND MEDIAEVAL CASTING (Metallurgy and Foundry Engineering, 2013)
In cooperation with the Archaeological Museum in Krakow, an attempt has been made to examine the earliest traces of non-ferrous metal metallurgy and casting in present-day Krakow. The preparatory investigation has centred around a group of finds coming from a small section of the eastern part of the city, including the area of present-day Nowa Huta. The paper gives an overall view of objects ranging from the first copper artefacts from the territory of Poland in the 4th millennium BC through Lusatian bronzes and Celtic products to modern slag from Jan Thurzo’s copper smelter. The analysis, involving diverse copper or copper alloy artefacts, ornaments and tools – both imports and local products – has been aimed at preliminary identification of Krakow’s earliest metal artefacts in terms of their materials and methods of production, and at preparing the ground for further study. This multifaceted research is intended to result in a comparison of materials and techniques used in metallurgy and casting during the timespan of 5000 years.